MOBILISASI PENYEBARAN INFORMASI KAMPUS BERBASIS FIREBASE CLOUD MESSAGING (FCM) - Fajar Abdul Aziz; Munawarah -; Primaadi Airlangga (SAINTEKBU, 2019)
Knowing information is important for students, especially information about the college. The fame of using SMS gateway as the information spread media which has much deficiency, such as the needs of credit as the sending media and cannot searching message. Nowadays some message delivery media based on Android come up with the lack in some aspects. For an instant, the user of a group can send a message in the group’s chat rooms so that the important message can jumble with the other information. In this research, we will offer an application that is able to give real-time information. The information used one line system so that it cannot jumble with the other information. The information contain the alarm that has benefit to remind the user and then the message searching feature to help the user to look for the previous information, the usage of website technology as the data organizing be able to be accessed by the administrator, furthermore the usage of mobile device with android based can be accessed more easily and also the usage of API from firebase to send a message in the real time. This research resulted in applications that can support needs such as providing information specifically in realtime and have an alarm feature activity. Keywords : Notifikasi, Firebase Cloud Messaging, Android, PHP, MySQL